2019
DOI: 10.1038/s41598-019-46140-9
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest stem cells from human epidermis of aged donors maintain their multipotency in vitro and in vivo

Abstract: Neural crest (NC) cells are multipotent stem cells that arise from the embryonic ectoderm, delaminate from the neural tube in early vertebrate development and migrate throughout the developing embryo, where they differentiate into various cell lineages. Here we show that multipotent and functional NC cells can be derived by induction with a growth factor cocktail containing FGF2 and IGF1 from cultures of human inter-follicular keratinocytes (KC) isolated from elderly donors. Adult NC cells exhibited longer dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Human NC stem cells have also been derived from direct reprogramming of fibroblasts by introduction of transcription factors, such as Sox10 230 or FoxD3, 231 which both play roles in maintenance of stem cell properties in NC cells (section 3). More recently NC cells were derived from keratinocytes of the interfollicular epidermis (another easily accessible source) of neonatal and adult donors by using growth factors for reprogramming 232,233 . These derived human NC stem cells have a molecular profile compatible with NC cell identity in animal models, they express genes such as Sox10, FoxD3, and AP2α and give rise to several NC derivatives such as neurons, glia, melanocytes, cartilage, and bone 46,225‐233 .…”
Section: Extended Stem Cell Potency Of Nc‐derived Cells Through Develmentioning
confidence: 99%
See 1 more Smart Citation
“…Human NC stem cells have also been derived from direct reprogramming of fibroblasts by introduction of transcription factors, such as Sox10 230 or FoxD3, 231 which both play roles in maintenance of stem cell properties in NC cells (section 3). More recently NC cells were derived from keratinocytes of the interfollicular epidermis (another easily accessible source) of neonatal and adult donors by using growth factors for reprogramming 232,233 . These derived human NC stem cells have a molecular profile compatible with NC cell identity in animal models, they express genes such as Sox10, FoxD3, and AP2α and give rise to several NC derivatives such as neurons, glia, melanocytes, cartilage, and bone 46,225‐233 .…”
Section: Extended Stem Cell Potency Of Nc‐derived Cells Through Develmentioning
confidence: 99%
“…More recently NC cells were derived from keratinocytes of the interfollicular epidermis (another easily accessible source) of neonatal and adult donors by using growth factors for reprogramming 232,233 . These derived human NC stem cells have a molecular profile compatible with NC cell identity in animal models, they express genes such as Sox10, FoxD3, and AP2α and give rise to several NC derivatives such as neurons, glia, melanocytes, cartilage, and bone 46,225‐233 . Although future work will need to determine how similar the NC cells formed by these various methods are to each other and how accurately they represent endogenous NC development, it is clear that these approaches hold great promise for regenerative therapy purposes.…”
Section: Extended Stem Cell Potency Of Nc‐derived Cells Through Develmentioning
confidence: 99%
“…Therefore, this approach provides a rapid method of obtaining NCLSCs that can be potentially administered clinically. To date, NCLSCs have been derived from human and mouse fibroblasts, 177,186‐188 keratinocytes, 189,190 and melanocytes 191 via the introduction of transcription factors, such as SOX10 and FOXD3 , specific growth factors, or forced expression of Notch1 signaling, respectively. It has been reported that the derived NCLSCs are functional in vivo when they were investigated for neural repair in a zebrafish model 186 and migration capability in a chick embryo model system 177,191 ; however, more detailed and comprehensive analysis of in vivo functional outcomes is still necessary.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chr7:134379901-134380671 was predicted to regulate CALD1 . CALD1 was known to play an essential role in the regulation of smooth muscle and non-muscle contraction 59 , which was a derivative of neural crest 60 . chr17:597438-597652 regulated FAM57A , which was linked to “Sclerosteosis 1”, a disease with abnormal character of skull and mandible 61 .…”
Section: Resultsmentioning
confidence: 99%